INFLUENCING FACTORS AFFECTING THE IMPLEMENTATION OF REPUBLIC ACT 9003(ECOLOGICAL SOLID WASTE MANAGEMENT ACT) IN THE PROVINCE OF LAGUNA - Severina Verna P.Oandasan (EPRA International Journal of Research and Development (IJRD), 2023)
This study aimed to determine the influencing factors affecting the implementation of Republic Act 9003 (Ecological Solid Waste Management Act of 2000) in the province of Laguna. It aimed to study the extent of influencing factors, the level of compliance, and the challenges encountered by LGUs in SWM implementation. The results of the study revealed that the respondents regarded the influencing factors such as institutional, technical, legal, financial, external assistance, and public participation and awareness as very influential to SWM implementation. However, most of it does not significantly predict the level of implementation of RA 9003. Among the challenges experienced by the LGUs, financial or budget insufficiency was the only serious problem identified. Based on the results of the study, the following are recommended to improve the level of compliance of LGUs with the provisions of RA 9003: the institutionalization of MENR Offices, capacitation of personnel assigned in the SWM section, allocation of sufficient budget for SWM programs and projects, strict enforcement of local ordinances, and conduct of intensive IEC to encourage the community to participate in solid waste management programs.